Analytical solution for distributed torsional low strain integrity test for pipe pile - Zhang, Yunpeng; Jiang, Guosheng; Wu, Wenbing; El Naggar, M. Hesham; Liu, Hao; Wen, Minjie; Wang, Kuihua (International journal for numerical and analytical methods in geomechanics, 2022)
Low strain integrity tests (LSITs) are the most popular non‐destructive methods for pile testing. However, traditional LSITs have encountered unprecedented challenges as the need for long pile and existing pile testing keeps multiplying. Compared to traditional longitudinal excitations, the torsional wave is less influenced by the velocity attenuation effect and can be subjected at the pile shaft for existing piles. Distributed torsional LSIT is proposed in this article with the presentation of the corresponding analytical solutions that exhibiting the velocity responses along the pile shaft. The solution is verified with previous simplified theoretical and rigorous finite element method (FEM) answers. At the end, the application of this method is exhibited through the identification of necking and concrete segregation defects on pipe piles, which shows the advantage of this method on long pile testing.